(untitled) (Journal of the College of Basic Education, 2026)
It is no secret that poetry serves as a mirror reflecting the reality of societies and expressing their concerns. It is one of the most important literary forms that conveys a true image of people’s feelings and aspirations. Among the trends that emerged in ancient Arabic poetry is the "popular style," which represents a poetic trend based on simplicity of language, clarity of meaning, and closeness to people’s reality and daily problems. This style was present in various eras, but it was particularly prominent in the Abbasid era thanks to the flourishing of culture and the widening gap between social classes. This led some poets to adopt a poetic style that represented the lives of ordinary people and conveyed their familiar conversations. One of the most famous of these poets was Abu al-Atahiyah, who was able to bring poetry closer to the common people with his distinctive style, expressing feelings of asceticism and wisdom, and drawing on popular heritage in his portrayal of societal issues. He transcended traditional praise in his poetry and moved towards more realistic themes that addressed people’s suffering, joys, and sorrows. Therefore, the focus of this research will be on the features of the popular style in Abu al-Atahiyah’s poetry and its role in revealing.